APAKAH PEKERJA MIGRAN INDONESIA SEHAT MENTAL? - Muhammad Iqbal (Research Center for Regional Resources-Indonesian Institute of Sciences (P2SDR-LIPI), 2019)
This study aims to describe the mental health of Indonesian migrant workers in Hong Kong. The respondents of this study were Indonesian female migrant workers who worked in domestic sectors in Hong Kong, the number of respondents in this study were 100 respondent, female Indonesia migrant workers. This study uses survey method and quantitative approach with a sampling technique aimed at criteria of minimum 1 year working period, women and working in the household or domestic sector. This research was carried out using a mental health questionnaire. Mental Health Inventory (MHI) constructed by RAND Health Insurance Experiment (Veil & Ware, 1983) 38 items that measure aspects of anxiety, depression, emotional control, affect. Data analysis using SPSS is by using description analysis and different test (T-test). Result shown that in general respondents showing a good mental health condition (81%), very good mental health condition (1%), and poor mental health condition (18%).Keywords: mental health, Indonesian migrant workers, women domestic workersAbstrakPenelitian ini bertujuan untuk mengetahui gambaran kesehatan mental pekerja rumah tangga perempuan migran Indonesia di Hong Kong. Responden penelitian ini adalah pekerja migran perempuan Indonesia yang bekerja sebagai pekerja rumah tangga di Hong Kong, jumlah responden penelitian ini adalah sebanyak 100 orang pekerja rumah tangga perempuan asal Indonesia. Penelitian ini menggunakan metode survey dengan pendekatan kuantitatif dengan teknik sampel bertujuan kriteria minimal masa kerja 1 tahun, perempuan dan bekerja pada sektor rumah tangga. Penelitan ini dilakukan dengan menggunakan alat ukur kuesioner kesehatan mental Mental Health Inventory (MHI) dikontruksi oleh RAND Health Insurance Experiment (Veil & Ware, 1983) yang terdiri dari 38 item yang mengukur aspek kecemasan, depresi, kontrol emosi, afek. Analisis data menggunakan SPSS yaitu dengan menggunakan analisis deskripsi dan uji beda (T-test) dan berdasarkan hasil analisa menggunakan SPSS menunjukkan bahwa secara umum responden mengindikasikan kondisi kesehatan mental yang kurang baik (18%), baik (81%), dan sangat baik (1%). Kata kunci: Kesehatan mental, pekerja migran Indonesia, pekerja rumah tangga perempuan